Comparative analysis of the performance of selected database management system - Piotr Marcin Tracz; Małgorzata Plechawska-Wójcik (Journal of Computer Sciences Institute)
Currently, in the era of large amounts of generated data, a significant challenge is fast data processing. The aim of the article is to conduct a comparative analysis of the performance of relational and non-relational databases using MS SQL Server, MongoDB, and CouchDB as examples. The comparison was carried out based on developed research scenarios designed to examine the execution time of CRUD operations. A performance ranking of databases was established based on the obtained results, with SQL Server taking the first place, MongoDB the second, and CouchDB the third. For the operations of deletion, downloading, and updating of data, MS SQL Server proved to be the most efficient database. Only in the operation of inserting data did MongoDB turn out to be the most efficient database.